Commitment and alignment of PUC-Rio’s postgraduate programme with sustainable development - Frota, Mauricio Nogueira (2014)
In line with the the me “postgraduate education and sustainable development” of this issue of the Revista Brasileira de Pós-Graduação, this article reflects the Pontifical Catholic University of Rio de Janeiro’s – PUC-Rio – commitment to sustainable development. It highlights the actions taken in response to recommendations from The United Nations Conferences on the environment and sustainable development (1972, 1980, 1992 and 2012) and from the “Global Colloquium of University Presidents” (New York University, 1987),attended by rectors of leading universities in the world. Being aware of its responsibility, PUC-Rio has oriented its commitment to environmental ethics to target the transformation of anthropocentric culture for the wholeness of human beings through biodiversity and environmental preservation. In the context of an integrated action by the university, the article discusses the consolidation of the sustainability pillar in its Postgraduate Programme in Metrology for Quality and Innovation.